Internalization of Religious Moderation Values through Hidden Curriculum at Pondok Pesantren Modern Al-Fahd Jakabaring Palembang - Amin, Khoirul; Abdurrahmansyah, Abdurrahmansyah; Fauzi, Muhammad (Lembaga Penelitian dan Pengabdian Masyarakat Institut Agama Islam Al-Khairat Pamekasan, 2024)
This research will describe the indirect process in which the values of religious moderation are not explicitly taught to the Santri through the norms, habits, and culture observed and lived in the pesantren environment. This research uses a qualitative approach. Data collection in this study was carried out through observation, interviews, and documentation. Data analysis in this study uses data collection, data reduction, data presentation, and conclusion drawing. The results showed that the values of religious moderation internalized in pesantren through the Hidden Curriculum, such as tolerance, peace, interfaith cooperation, and a moderate attitude in addressing differences in religious beliefs, are reflected in daily life in pesantren. The hidden curriculum includes all aspects of teaching and learning that are not explicitly listed in the formal curriculum but still significantly impact the formation of student characters, attitudes, and values. In religious moderation, this refers to internalizing values that create a moderate, tolerant, and open attitude toward religious differences. The Hidden Curriculum is an alternative model for internalizing the Merdeka curriculum, which is more flexible in instilling Curriculum values.